2014
DOI: 10.1136/neurintsurg-2014-011374
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasospasm patterns following aneurysmal subarachnoid hemorrhage: an angiographic study comparing coils with clips

Abstract: Patients with aSAH treated by endovascular coiling and surgical clipping demonstrate distinct vasospasm patterns. While both initially exhibit perianeurysmal spasm, patients treated by coiling go on to develop stepwise progression distally over time. This finding may reflect dispersion of blood breakdown products along preserved CSF egress pathways in patients treated by endovascular coiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…Although we were not able to reliably draw statistical conclusions, two other factors suggest less CV risk for the Fisher 2 patients in this cohort: (i) none of the seven Fisher 2 patients had DCI and (ii) the lack of CV diagnostic imaging studies performed in these patients imply that there was no clinical need. With respect to aneurysm size and treatment modality, previous studies have shown conflicting evidence regarding the risk for CV (31)(32)(33)(34)(35)(36). Here, we found a correlation between coiling and increased CV, which is in contradiction to larger studies that demonstrate no difference between groups or favor coiling for lower risk (31,32,35,36).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although we were not able to reliably draw statistical conclusions, two other factors suggest less CV risk for the Fisher 2 patients in this cohort: (i) none of the seven Fisher 2 patients had DCI and (ii) the lack of CV diagnostic imaging studies performed in these patients imply that there was no clinical need. With respect to aneurysm size and treatment modality, previous studies have shown conflicting evidence regarding the risk for CV (31)(32)(33)(34)(35)(36). Here, we found a correlation between coiling and increased CV, which is in contradiction to larger studies that demonstrate no difference between groups or favor coiling for lower risk (31,32,35,36).…”
Section: Discussioncontrasting
confidence: 99%
“…With respect to aneurysm size and treatment modality, previous studies have shown conflicting evidence regarding the risk for CV (31)(32)(33)(34)(35)(36). Here, we found a correlation between coiling and increased CV, which is in contradiction to larger studies that demonstrate no difference between groups or favor coiling for lower risk (31,32,35,36). We are uncertain of why coiled patients in this study tended to have more CV, although we cannot exclude that those patients less prone to CV were more often surgically clipped.…”
Section: Discussioncontrasting
confidence: 99%
“…This seems to be related to a varying cerebrospinal fluid circulation for carrying away blood degradation products, presumably depending on the method of treatment. 21 The impact on the clinical course has yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al analyzed the pathogenesis of cerebral vasospasm, and reported the process of SAH washout. 12) According to their study, cerebral vasospasm around a treated aneurysm remained after clipping, whereas it gradually migrated to a distal blood vessel after coiling. This suggests that coiling does not affect cerebrospinal fluid circulation, facilitating the spontaneous washout of SAH along this circulation.…”
Section: Discussionmentioning
confidence: 99%